Talempong as Inheritance Intangible Culture : Identity, Aesthetics and Function Minangkabau Social Society - Rina Armeniza Aziz; John JOI Ihalauw; Sugiarto Sugiarto (Momentum Matrix: International Journal of Communication, Tourism, and Social Economic Trends, 2026)
Talempong, the Minangkabau bronze gong tradition of West Sumatra, is an important but under-documented intangible cultural heritage. This study examines Talempong's historical evolution, aesthetic value, and role in maintaining Minangkabau identity amidst modernization and the commodification of tourism. Three main focuses are: the development of Talempong from prehistory to the contemporary; the aesthetic principles underlying the performance; and its function as a marker of ethnic and communal identity. Qualitative interpretive methods are employed through a review of ethnomusicology, anthropology, and tourism literature, as well as an analysis of documents on Talempong practice. The findings reveal five historical layers from megalithic idiophones to tourism oriented diatonic ensembles; an aesthetic based on oral tuning systems (limo salabuan, onam salabuan) and colotomic patterns that emphasize communal cooperation; and Talempong's function as a nagari identity, a traditional medium, and a cultural tourism resource. The discussion situates these findings within debates on intangible heritage preservation in Indonesia and Southeast Asia. The conclusion confirms that Talempong's sustainability depends on a balance of authenticity and adaptive innovation, with recommendations for community-based documentation, educational transmission, and heritage tourism governance.